STATISTICAL STUDY OF DEMOGRAPHIC PROCESSES OF THE POPULATION OF THE REPUBLIC OF UZBEKISTAN - Siroj Zarina Rustambekovna (Zeta Repository, 2023)
This article describes the study of the demographic processes of the population of the Republic of Uzbekistan.